Rancang Bangun Sistem Informasi Peminjaman Arsip Berbasis Web - Martin, Martin; Nilawati, Lala (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
Good archival data management can be seen when users make it easier when they need information in the archive. The archives management section at the National Human Rights Commission requires an application for managing archive borrowing, because currently the process of borrowing archives requires a long process, so it becomes ineffective and requires a long data search if there is an error in recording the loan or returning the borrowed archive. The use of a web-based archival lending information system is very necessary, because processing archival lending data makes it very easy to collect loan data and can continue to monitor and control the status of the archival loan data. This web-based archive lending information system is designed by applying the ADDIE version development method (Analyze, Design, Development, Implementation, Evaluate) and the waterfall development model in the system design stage, and the system will be built using the programming languages PHP 7.3, MySQL 5.7, Nginx and PHP-FPM 7.4, Laravel Framework 7 and Bootstrap Template Design 4.0. This system is expected to provide convenience and the best service to internal parts of the institution that need information in the desired archives